PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI - SUKRISPIYANTO; BUDI SETYAWAN (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2021)
The purpose of this study (1) is to determine the effect of partial communication on the performance of the Bantur Subdistrict Office, Malang Regency, (2) to determine the partial effect of the work environment on the performance of the Bantur Subdistrict office, Malang Regency, (3) To determine the communication and work environment in a partial way. Simultaneous significant effect on the performance of the employees of the Bantur District Office, Malang Regency. The method used in this research is quantitative. The sampling technique is census or saturated sample with 30 respondents. The data in this study used a questionnaire measuring instrument using a Likert scale. Data analysis used validity test, reliability test, classiﬁcation assumption, multiple linear regression, T test and F test. Based on the test results, the t-count value of 4.417 is greater than t-table 2.052 which shows a significant effect as well as the F-test results which show that the calculated F is 27,382 and the F table is 3.35 showing significant results.